Demographic profile and respiratory pathogen etiology of acute respiratory infection in children in a private hospital in Jakarta - Madeleine Ramdhani Jasin; Abicintha Pramesti Sheila; Reza Agustiantwo Putra (Indonesian Pediatric Society, 2026)
Background Acute respiratory infections (ARI) are commonly diagnosed in children and contribute to high morbidity and mortality in the pediatric population. Diagnosis of ARI is made clinically, and exploration for the causative pathogen is not always performed. If the specific pathogen in ARI is identified, it can inform the management strategies in affected patients. Objective To detect specific respiratory viruses and bacteria by PCR in children with ARI and to describe the clinical manifestations and laboratory results in affected childrens. Methods This cross-sectional study commenced by collecting a 1-year period of medical record data of children with ARI diagnosis in Mayapada Hospital, South Jakarta, from January 2023 to January 2024. Symptoms of ARI, laboratory examinations of leukocytes and CRP levels, and QiastatTM respiratory panel test results were collected and evaluated to find out etiology of ARI, whether virus or bacteria. Results A total of 161 subjects were included in our study, who were mostly age < 5 years (62.7%), male (55.9%), and positive for pathogens in 83.9% of subjects. Cough (90.7%), fever (90.1%), and rhinorrhea (65.2%) were the most prevalent symptoms. Shortness of breath was also documented, but in only 37.3% of subjects. Leukocyte levels were mostly normal, while CRP levels were mostly high. The most prevalent pathogens found were influenza A virus, adenovirus, and rhinovirus/enterovirus. Co-infection was found in 9.3% of subjects, commonly in adenovirus and human metapneumovirus A+B; rhinovirus/enterovirus and adenovirus; as well as rhinovirus/enterovirus and RSV A+B. Conclusion Identifying pathogens is beneficial to identify ARI etiology, which may lead to different treatment and infection control. Children with ARI are mostly male and aged < 5 years. Respiratory pathogen results are high, in 83.9% subjects, also the most prevalent are influenza A virus, adenovirus, and rhinovirus/enterovirus.